Consumption of ultra-processed foods and the risk of overweight, obesity, and weight trajectories. (13th November 2019) - Srour, B; Beslay, M; Allès, B; Chazelas, E; Deschasaux, M; Hercberg, S; Monteiro, C A; Kesse-Guyot, E; Touvier, M; Julia, C
Abstract: : Previous epidemiological studies found associations between the consumption of ultra-processed foods (UPF) and the risk of obesity-related outcomes. The aim of this study is to investigate the associations between UPF consumption and the risk of overweight and obesity, and weight trajectories, in in the French large scale NutriNet-Santé cohort. Methods: Overall, 110260 participants aged at least 18 years from the French NutriNet-Santé cohort (2009-2019) were included. Dietary intakes were collected using repeated 24h dietary records, merged with a food composition database of 3300 different products, categorized according to their degree of processing by the NOVA classification. Associations between UPF intake and risks of overweight and obesity were assessed using Cox proportional hazard models. Associations between UPF intake and weight trajectories were assessed using linear mixed models for repeated measures with random slope and intercept. Results: UPF intake was associated with a higher risk of overweight (n = 7063 incident cases; hazard ratio for an absolute increment of 10 in the percentage of ultra-processed foods in the diet = 1.11 (1.08-1.14); P < 0.0001) and obesity (n = 3066 incident cases; HR = 1.09 (1.05-1.13); P < 0.0001). Higher consumers of UPF (4th quartile) were more likely to present an increase in body mass index over time (β = 0.04, P < 0.0001). These results remained statistically significant after adjustment for several markers of the nutritional quality of the diet (fruits and vegetables and sugary drinks consumption, intakes of saturated fatty acids, sodium, sugar, dietary fiber or Healthy/Western patterns) and after a large range of sensitivity analyses. Conclusions: In this large observational prospective study, higher consumption of UPF was associated with a higher risk of overweight and obesity. Public health authorities in several countries recently started to recommend privileging unprocessed/minimally processed foods and limiting UPF consumption. Key messages: The consumption of ultra-processed food is associated with an increased risk of overweight and obesity. As the French Public Helath agency recommends, their consumption should be limited. Nutritional composition, food additives, contact materials, or neoformed contaminants might play a role in these associations and further studies are needed to understand their relative contribution.